Um olhar sobre a solidão feminina e os relacionamentos interpessoais nas histórias de brasileiras e mexicanas - Dornelas, Kirlla Cristhine Almeida (2010)
Human beings are social. That comment cliché pay attention to the importance of interpersonal relationships in the constitution of the individual. Therefore, the limitation in interpersonal relationships, consequently cause great suffering, loneliness. Studies on the phenomenon have loneliness as an unpleasant feeling due to undesirable or disabled relationships. Moreover, the loneliness can occur in the presence or absence of people. Despite the representation of loneliness as something bad, this experience can also be seen as positive in this case it is the solitude. Loneliness is a special experience for each person from their sociocultural and environmental. The transformations of the female roles, such as entering the world of work, for example, may have magnified the social network of women and displaced, their interests, apart from their husbands and children. Still, the social pressure seems to be stronger on women. This work aims to investigate the experience of loneliness for Brazilian and Mexican women in interpersonal relationships: friendship, romantic relationship and family. Objectives: (a) review the experience of loneliness in their social and emotional aspects, (b) to relate the different types of interpersonal relationships and the experience of loneliness, (c) examine the coping strategies of loneliness, (d) analyze the importance of solitude and its consequences for interpersonal relationships. Loneliness is a complex and multidimensional phenomenons, before this, the dialectical perspective of Hinde on interpersonal relationships guide our analysis. Our data source are reports of Brazilian and Mexican about the loneliness in relation to friends, the loneliness in romantic relationships, loneliness and family, and the coping strategies. In addition, the participants write about the times when seek to be alone, the importance of this and evaluated their relationship networks. 30 participants were in the study, 15 Mexican and 15 Brazilian, between 25 and 40 years, enrolled in graduate courses. The entire search was done via email. The data show that loneliness is part of the types of relationships and has researched several meanings according to the relationship and the context in which it occurs. Some limitations in interpersonal relationships are suggested. The participants used different strategies for coping with loneliness. Solitude is also part of interpersonal relationships. The analysis seeks to take a look at the women's loneliness and propose a model for understanding the phenomenon.